2004
DOI: 10.2174/0929867043365116
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products in the Process of Finding New Drug Candidates

Abstract: Natural derived or originated compounds still play a major role as drugs, and as lead structures for the development of synthetic molecules. About 50% of the drugs introduced to the market during the last 20 years are derived directly or indirectly from small biogenic molecules. In the future, natural products will continue to play a major role as active substances, model molecules for the discovery and validation of drug targets. A multidisciplinary approach to drug discovery involving the generation of truly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
194
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(197 citation statements)
references
References 87 publications
0
194
0
3
Order By: Relevance
“…These products are relatively not toxic, inexpensive and available in an ingestive form. During the two last decades, more than 25 % of drugs used are directly derived from plants, while the other 25 % are chemically altered natural products (Vuorelaa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These products are relatively not toxic, inexpensive and available in an ingestive form. During the two last decades, more than 25 % of drugs used are directly derived from plants, while the other 25 % are chemically altered natural products (Vuorelaa et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The search for new medicinal products has been extrapolated from plants, animals, and micro-organisms, with historical evidence suggesting the use and benefits of natural products [3]. It has led the pharmaceu-tical industry to several plant-derived medications through modern analytical and structural analysis of plant-based compounds [3,4]. The discovery of morphine in 1805 by German pharmacist Fredrich Wilhelm Sertürner (1783-1841) became the first plant-based medical discovery and influenced several natural-based medical discoveries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies between animals and plants has revealed that both species use similar signaling molecules and recaptors, suggesting that plant chemical compounds have the ability to bind to human disease to modulate binding and metabolism [3]. Nearly 50% of the drugs introduced in the past 20 years have been derived directly or indirectly from natural products, and several in vitro tests such as medium pressure solid-liquid extraction (MPSLE), rotation planar extraction (RPE), and thin layer chromatography (TLC) are currently available for screening plants and their properties for drug extrapolation and investigation [4]. Despite this fact, very little effort has been made to looking at the influence of pharmacogenetics in the efficacy and toxicity of natural medicines.…”
Section: Introductionmentioning
confidence: 99%
“…7,8) Of particular interest of gastroprotective diterpenes are the clerodanes (trans-dehydrocrotonin from Croton cajucara, and aparisthman from Aparisthmium cordatum), the labdanes (solidagenone from Solidago chilensis and 15-acetoxylabd-8(17)-en-19-ol as well as 15,19-diacetoxylabd-8(17)-en from Araucaria araucana), abietane (ferruginol from Prumnopitys andin), and Jatrophone from Jatropha isabelli, 9,10) which may play a major role in drug discovery as well, in providing lead structures for the development of synthetic molecules. 11,12) In several parts of Brazil, tea or decoction prepared from the flower buds of Egletes viscosa (Asteraceae) is a popular remedy for the treatment of digestive and intestinal problems.13) Phytochemical studies on flower buds revealed the presence of diterpene compounds, centipedic acid (CPA) and 12-acetoxy-hawtriwaic acid lactone (tanabalin), and a tetramethoxy flavone, ternatin.14) Pharmacological investigations identified the anti-inflammatory, hepatoprotective, antidiarrhoeal and gastroprotective properties of ternatin. 15,16) In a previous study, we established the gastroprotective effects of both CPA and tanabolin against indomethacin and ethanolinduced gastric lesions, validating the traditional use of E. viscosa.…”
mentioning
confidence: 99%
“…7,8) Of particular interest of gastroprotective diterpenes are the clerodanes (trans-dehydrocrotonin from Croton cajucara, and aparisthman from Aparisthmium cordatum), the labdanes (solidagenone from Solidago chilensis and 15-acetoxylabd-8(17)-en-19-ol as well as 15,19-diacetoxylabd-8(17)-en from Araucaria araucana), abietane (ferruginol from Prumnopitys andin), and Jatrophone from Jatropha isabelli, 9,10) which may play a major role in drug discovery as well, in providing lead structures for the development of synthetic molecules. 11,12) In several parts of Brazil, tea or decoction prepared from the flower buds of Egletes viscosa (Asteraceae) is a popular remedy for the treatment of digestive and intestinal problems.…”
mentioning
confidence: 99%